Adaptation, learning, Bildung: Discussion with edu- and biosemiotics. - Pikkarainen, Eetu (Sign Systems Studies, 2018)
Learning and adaptation are central problems to both edusemiotics, or semiotics of education, and biosemiotics. Bildung, as an especially human way or form of learning, and evolution as the main form of adaptation for many biologists aft er Darwin are oft en regarded as mutually exclusive concepts even though human beings are undeniably one biological species among others. In this article I will try to build a bridge between the biosemiotical, edusemiotical and Bildung-theoretical stances. Central to this discussion is biosemiotician Kalevi Kull and some of his recent publications where he considers adaptation, evolution and learning. Th e primary theoretical resource that I utilize here, in addition to the general Greimassian, edusemiotical and Bildungtheoretical starting points, is perceptual control theory (PCT) to which I compare the Uexküllian conception of functional circle.